A Cluster of Cases of Rocky Mountain Spotted Fever in an Area Of Colombia Not Known to be Endemic for This Disease (2019)
ABSTRACT: Rocky Mountain spotted fever (RMSF) has been reported in Colombia since 1937. Most recent outbreaks were in 2006-2008, followed by the absence of recognized cases. This report describes new clinical cases of RMSF and epidemiologic investigations. Medical records were reviewed, and fieldwork, serological and molecular diagnostic testing, and bacterial isolation were performed. Fever, hypotension, abdominal discomfort, and rash accompanied by thrombocytopenia and leukopenia were the most characteristic manifestations. Two convalescent sera from the index case and sera from two dogs revealed high anti-spotted fever group Rickettsia antibody titers. Rickettsia rickettsii was isolated from case 4. Cases 2 and 3 were identified by epidemiological connection with the index case. Thus, a new cluster of cases of RMSF was identified in Antioquia, Colombia, with the occurrence of fatal cases, which indicates the active circulation of the bacteria and a potential risk for the population.